2001
DOI: 10.1207/s15327108ijap1103_04
|View full text |Cite|
|
Sign up to set email alerts
|

Autogenic Feedback Training Exercise and Pilot Performance: Enhanced Functioning Under Search-and-Rescue Flying Conditions

Abstract: Studies have shown that autonomous mode behavior is one cause of aircraft fatalities due to pilot error. In such cases, the pilot is in a high state of psychological and physiological arousal and tends to focus on one problem, while ignoring more critical information. This study examined the effect of training in physiological self-recognition and regulation, as a means of improving crew cockpit performance. Seventeen pilots were assigned to the treatment and control groups matched for accumulated flight hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…It is also known that fear states are characterized by low parasympathetic tone and a narrowing of perspective. This is a problem in some work situations such as search and rescue (Cowings, Toscano, Keller, & Burge, 2001), where it can cause workers to make costly errors. In this context, narrowed perspective has different content but otherwise resembles that hypothesized to occur in anxiety disorder (Clark, 1989).…”
Section: Number Of Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that fear states are characterized by low parasympathetic tone and a narrowing of perspective. This is a problem in some work situations such as search and rescue (Cowings, Toscano, Keller, & Burge, 2001), where it can cause workers to make costly errors. In this context, narrowed perspective has different content but otherwise resembles that hypothesized to occur in anxiety disorder (Clark, 1989).…”
Section: Number Of Sessionsmentioning
confidence: 99%
“…There are conflicting views in the literature on anxiety disorders about the primacy of cognition versus emotion. A basic assumption of the cognitive model of anxiety is that cognitive processes and structures mediate behaviour and emotions (Clark & Steer, 1996). However, this does not account for difficulties people can have in reporting specific thoughts that preceded an emotional reaction (Barlow, 2002).…”
mentioning
confidence: 99%
“…Cardiovascular psychophysiology, the recording of cardiovascular responses during behavioral research, is based on the premise that cardiovascular responses differ in direction and magnitude contingent on stimulus characteristics but remain sensitive to the specificity associated with individual response patterns (Cacioppo, Tassinary, & Berntson, 2007). The responses that are typically used with cardiovascular psychophysiological paradigms are heart rate (HR) and blood volume pulse (BVP), a measure of vasodilatation and vasoconstriction; BVP relative amplitude is inversely correlated with HR (Cowings, Kellar, Folen, Toscano, & Burge, 2001;Cowings & Toscano, 2000;Cowings et al, 2007). Distinct cardiovascular changes during encoding are measurable within a few seconds of stimulus onset, allowing precise quantification of event and no event (baseline) conditions within an implicit priming paradigm.…”
mentioning
confidence: 99%
“…In fact, our research on AFTE has demonstrated that learning control of autonomic responses significantly improves performance under stress. 18,19 Data taken from postflight crew debriefings and flight medical logs indicate that IM promethazine may have less deleterious effects in space than on Earth, 3 but drugs affect multiple systems, not just the targeted response. Promethazine may decrease performance when it is measured in space, while AFTE trains the subject to control physiological variables, focusing on specific systems with no observed untoward effects.…”
Section: Discussionmentioning
confidence: 99%
“…AFTE methods were used to train subjects to selfregulate their physiological response levels. [7][8][9][10][11][18][19][20] Each daily training session was 30 minutes and was administered on 4 consecutive days a week for 3 weeks (total 6 hours). The sessions were divided into ten 3-minute trials, during which subjects were taught to alternate increases and decreases in their response levels (e.g., heart rate accelerations and decelerations, peripheral vasodilatation and constriction, increases and decreases in skin conductance, etc.).…”
Section: Autogenic-feedback Training Exercise (Afte)mentioning
confidence: 99%